Analysis Of The Impact Of The Increase And Decrease In Rice Prices On Employee Income And Company Income In Sulawesi Selatan Province - Syamsu Rijal; Muhammad Ilyas Thamrin Tahir; Nurul Afifah (International Journal of Technology and Education Research, 2025)
The purpose of this study is to gain broader knowledge and understanding regarding the Analysis of the Impact of Rice Price Increases and Declines on Employee Income and Company Income at the UD. Putra Syarif Rice Company in Soppeng Regency. The method used in this study is qualitative with a descriptive qualitative research type. The sample used in this study was 5 respondents. Data collection techniques through observation, interviews and documentation. The results of this study are that the increase in rice prices has a significant impact on company income, because the increase in rice prices increases the company's profit margin. The decrease in rice prices also has an impact on company income. However, the impact is that the company's income has decreased. While on the other hand, the increase and decrease in rice prices have no impact on employee income. In facing this situation, the main strategy implemented by the company is to adjust the quality of rice when prices rise, and hold distribution when prices fall. In addition, the company prioritizes efficiency, good stock management, and strengthening relations with distributors and consumers. Harmonious working relationships, a family-like work climate, and open communication between leaders and employees are also important assets in facing market dynamics.